Cortical Thickness in Children of Parents Diagnosed with Bipolar Disorder - Oliver, Corinne; Hanford, Lindsay; Hall, Geoffrey B..; Sassi, Roberto B.. (The Meducator, 2013)
Bipolar disorder (BD) is associated with reduced cortical thickness in prefrontal and temporal cortical areas responsible for affect regulation. Children of parents diagnosed with bipolar disorder (high-risk (HR) offspring) are at risk of developing a psychiatric illness, and may have cortical abnormalities in affect regulating pathways prior to the onset of any psychiatric disorder. The current study is investigating cortical abnormalities in children at risk of developing bipolar disorder to better understand the developmental trajectories of psychopathology. Twenty-four HR bipolar offspring (average age = 13.7 (2.69) years, 12 females), and 9 age and sex matched healthy controls (HC) (average age = 12.9 (2.70) years, 5 females) were included in this study. Structural brain scans were administered and measures of cortical thickness were extracted and compared between the HR and HC offspring. HR offspring had significantly decreased cortical thickness in the left superior frontal gyrus, BA 6 (t=4.23 and t=3.57), the left posterior cingulate, BA 30 (t=3.49 and t=3.44) compared to HC offspring. Further analysis of subgroups of the HR population found additional areas of cortical abnormalities in the frontal and temporal cortex. The significant cortical differences found between HC children and HR bipolar offspring suggest that neurobiological markers of risk and resilience can be identified in children at risk of developing BD.